Nutritional and functional perspectives of barley β-glucan - Khan, M. R. K. (2021)
Barley (Hordeum vulgare), one of the important cereals in world after wheat, rice and maize. β-Glucan, a polysaccharide and soluble dietary fiber, has great potential as a nutraceutical ingredient. Its potential is not utterly utilized in food industry and used as fodder in developing countries with limited human consumption mainly due to lack of awareness. Consumers should prefer the foods rich in functional ingredients owing to their consciousness about health with good nutrition. β-glucan play a pivotal role as nutraceutical food in preventing cardiovascular diseases, controlling diabetes mellitus, regulating cholesterol level in body. New and novel research domains like molecular weight of β-glucan in relation to industrial important aspects will broaden the scope for utilization in different food systems. Research and studies related to different extraction methodologies and techniques for β-glucan, its functional properties and potential use in beverage manufacturing will enhance the health beneficial verdicts. Food industry can exploit β-glucan as for its functional properties i.e. thickening, stabilizing, emulsifying and gelling to maintain the stability of ingredients especially in beverage production. By manipulating the extracted β-glucan and protein contents from barley, numerous types of malt (beer) and different beverages can be prepared to satisfy different quality parameters of consumers. The physicochemical, nutritional, functional attributes, yield and purity of the β-glucan depends substantially to extraction procedures from the raw material ultimately exhibiting health benefits, which are associated with lowering of blood glucose level and CVDs boosting immune system for better gut health.